PENGARUH KEJELASAN TUJUAN ANGGARAN DAN PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi Empiris Pada Instansi Pemerintah Kota Bengkulu) - Melly Susanti; Husaini Husaini; Isma Coryanata (Unib Press Universitas Bengkulu, 2017)
This study aims to examine the influence of budget goal clarity and budget drafting participation on performance accountability of government institutions in Bengkulu city. This study is a descriptive research with purposive sampling technique. The subjects of this study were 136 officers of echelon III (Division Head/ Sub-division Head/ Secretary) and echelon IV (Chief Sub-division/ Chief Section) of civil servants in government institutions in Bengkulu city. Data analysis technique used in this study was multiple linear regression test. The results of this study showed that: (1) Budget goal clarity influences positively and significantly on performance accountability of government institutions in Bengkulu city. (2) Budget drafting participation influences positively and significantly on performance accountability of government institutions in Bengkulu city. These results indicate that the higher budget targe t clarity and participation in budget drafting, the higher performance accountability will be. Keywords: Budget Goal Clarity, Budget Drafting Participation, Performance Accountability.